(untitled) (Journal of the College of Basic Education, 2025)
The American policy towards Egypt occupies great importance at the regional and global levels, given the tension and conflict that the region has experienced as a result of the Arab-Israeli conflict, which affected Egypt’s relations with the countries of the world. During that period, relations between Egypt and the United States witnessed a kind of tension that led to the severing of relations between the two parties as a result of the continuous American support for (Israel). However, American diplomacy quickly returned and tried to remove the obstacles that led to the tension in the relationship between the two parties, especially after the change that occurred in the Egyptian positions and policy towards (Israel) and the attempts made by American policy to form and normalize relations between the two parties. It actually succeeded in doing so by concluding the Camp David Peace Treaty in 1979, which established the foundations of peace in the Middle East and opened new horizons for American policy towards Egypt on the political level, which was consistent between the two parties, in addition to the United States adopting a new policy towards Egypt on the economic, military and cultural levels.